Typification of the name Brachypodium obtusifolium (Brachypodieae, Poaceae) - Ferrer-Gallego, P. Pablo; Martínez Labarga, Juan M. (Phytotaxa, 2022)
Brachypodium Palisot de Beauvois (1812: 100,155) (Brachypodieae, Pooideae) is a temperate grass distributed in Europe and Asia with disjunct occurrences in Central America and Central and Southern Africa (Schippmann 1991, Catalán & Olmstead 2000, Piep 2007).  Brachypodium obtusifolium Lagasca ex Link (1821: 95) is a Spanish endemic species, restricted to the mountainous zone of Sierra Nevada, Sierra Tejeda, Sierra de Almijara and Sierra de Cázulas (provinces of Granada and Málaga) (Romero 2009; López González 2021).